The impact of climate-related security risks on community values: Insights from Zambia’s Southern Province - Tarusarira, Joram; Visser-Nieraeth, Anja; Kambela, Lweendo; Caroli, Giulia; Maviza, Gracsious (Brill, 2024)
This article explores the impact of climate-related security risks on community values and how that impact influences responses to the risks. Research and practice have paid little attention to how non-material and subjective conditions, especially values, mediate the climate-security nexus. We focused on the impact of land conflicts and food insecurity (as examples of climate-related security risks) on community values through a study of two rural communities in Zambia’s southern province using impact rating, focus-group discussions (FGDs), and interviews. Innovatively, we began by identifying community values and asking about the impact of climate security risks on community values instead of what ‘experts’ perceive or consider to be risks. We found that, firstly, participants from both communities perceived both land conflicts and food insecurity as having a strong to very strong influence on their values. Secondly, women perceive the impact of land conflicts and food insecurity on values to be greater than men do. Thirdly, the perception of the impact of climate-related security risks on values is prevalent among communities in Zambia’s southern province. The article concludes that values are crucial and central determinants in how communities interpret and respond to climate-related security risks, as well as how they engage with food, land, and water systems. It recommends that policymakers and practitioners integrate community values for effective and sustainable climate-related security risk policies and interventions.